Did the NICE guideline for progesterone treatment of threatened miscarriage get it right? - W Colin Duncan (Bioscientifica, 2022)
In November 2021, NICE updated its clinical guideline that covers the management of threatened miscarriage in the first trimester. They recommended offering vaginal micronised progesterone twice daily until 16 completed weeks of pregnancy in those with a previous miscarriage. However, the duration of treatment is not evidence based. In the major clinical trial that informed the guideline, there was no benefit in starting progesterone after 9 weeks and the full effect of progesterone was present at 12 weeks of pregnancy. There are theoretical risks impacting offspring health in later life after maternal pharmaceutical progesterone treatment. As the effect of progesterone seems to be complete by 12 weeks of gestation, we should consider carefully whether to follow the guidance and treat up to 16 weeks of pregnancy.